Nonfullerene Polymer Solar Cell with Large Active Area of 216 cm2 and High Power Conversion Efficiency of 7.7%. Issue 8 (17th May 2019) - Huang, Kuan-Min; Lin, Chih-Ming; Chen, Szu-Han; Li, Cheng-Sian; Hu, Chen-Hsuan; Zhang, Yu; Meng, Hsin-Fei; Chang, Chih-Yu; Chao, Yu-Chiang; Zan, Hsiao-Wen; Huo, Lijun; Yu, Peichen
Abstract : A polymer solar cell involving a nonfullerene acceptor is made by blade coating. In the ternary bulk‐heterojunction layer, the donor is poly[(2, 6‐(4, 8‐bis(5‐(2‐ethylhexyl)thiophen‐2‐yl)benzo[1, 2‐b:4, 5‐b']dithiophene))‐co‐(1, 3‐di(5‐thiophene‐2‐yl)‐ 5, 7‐bis(2‐ethylhexyl)benzo[1, 2‐c:4, 5‐c']dithiophene‐4, 8‐dione)] (PBDB‐T) and the acceptor is a mixture of 3, 9‐bis(2‐methylene‐(3‐(1, 1‐dicyanomethylene)‐indanone))‐5, 5, 11, 11‐tetrakis(4‐hexylphenyl)‐dithieno[2, 3‐d:2', 3'‐d']‐s‐indaceno[1, 2‐b:5, 6‐b']dithiophene) (ITIC) and [6, 6]‐phenyl C71 ‐butyric acid methyl ester (PC71 BM). The device structure is an indium tin oxide (ITO)‐coated glass substrate/PEDOT:PSS/ternary active layer/interfacial layer/Al. For a small active area of 0.04 cm 2, the best power conversion efficiency is 9.8% with the LiF interfacial layer. For a large active area of 216 cm 2, the best efficiency is 7.7% with the ZrOx interfacial layer. After annealing at 85 °C for 30 days, the large‐area device keeps 75% of the initial efficiency. The efficiency of 4.9% is achieved for a large‐area semi‐transparent device. Abstract : A polymer solar cell (PSC) with a large active area of 216 cm 2 and high power conversion efficiency of 7.7% is presented, involving a nonfullerene acceptor and the solution‐processable ZrOx interfacial layer made by blade coating. This represents the highest reported efficiency for PSCs with an active area more than 10 cm 2 . More encouragingly, the large‐area PSC shows good long‐term thermal stability as well.